Creative Shared Religious Education with Film-Making and History - John Wolffe; John Maiden; Stefanie Sinclair; Katelin Teller (Religions)
This paper discusses the development of an innovative methodology for engaging young people with issues of religious diversity and toleration, through combining engagement with historical and contemporary sources with the production of short documentary films reflecting on their own experience. We report on pilot workshops held in contrasting locations—London, Belfast, Skopje (North Macedonia), Durrës (Albania), and Amman (Jordan). In some of the workshops, participants worked directly with young people from other religious traditions; in others, participants themselves were drawn from a single religious tradition, but sought actively to engage with others, for example Orthodox Christians in North Macedonia spoke to Muslims and filmed inside a mosque; Muslims in Jordan similarly visited local Christians and their churches; Catholics and Protestants in Belfast were eager to understand and interact with the other community. In the light of overwhelmingly positive feedback from participants, the analysis applies contact theory to argue that the methodology facilitates deep learning and teambuilding, enhancing respect and understanding between different religious groups. It also demonstrates the value of religious education for enhancing young people’s understanding of other subjects, notably history and citizenship.